2021
DOI: 10.3389/fnhum.2021.701091
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Power Correlates With the Decoding Performance of Motor Imagery Both Across Time and Subjects

Abstract: One of the most significant challenges in the application of brain-computer interfaces (BCI) is the large performance variation, which often occurs over time or across users. Recent evidence suggests that the physiological states may explain this performance variation in BCI, however, the underlying neurophysiological mechanism is unclear. In this study, we conducted a seven-session motor-imagery (MI) experiment on 20 healthy subjects to investigate the neurophysiological mechanism on the performance variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Both imagined movement and imagined sensation are covert mental tasks, which are inherently internal and difficult to observe and measure when no external cue is applied. This causes a wide range of performance variations [33], [34], with relatively poor performance even when training across weeks [35]- [37].…”
Section: Introductionmentioning
confidence: 99%
“…Both imagined movement and imagined sensation are covert mental tasks, which are inherently internal and difficult to observe and measure when no external cue is applied. This causes a wide range of performance variations [33], [34], with relatively poor performance even when training across weeks [35]- [37].…”
Section: Introductionmentioning
confidence: 99%
“…Further, some researchers found that lower resting-state alpha-band relative power (RP) may indicate poor MI performers (Ahn et al, 2013;Kwon et al, 2020). Our previous study suggests that the positive correlation between alpha-band RP and MI-BCI performance was consistent in inter-subject and inter-session analysis, especially over the frontal lobes (Zhou et al, 2021). These results indicate that the strength of alpha rhythm in the resting state might reflect an unstable cognitive state, which results in the variation of MI-BCI performance.…”
Section: Introductionmentioning
confidence: 87%
“…Our previous study showed no obvious MI-BCI performance improvement across six runs in 1 day or even across seven sessions in multiple days without feedback (Zhou et al, 2021), suggesting that subjects found it difficult to regulate their brain rhythms to successfully reach the expected output without feedback. In this study, MI-BCI performance was significantly improved after alpha NFT, especially between left-hand and right-hand MI tasks.…”
Section: Effectiveness Of Alpha Neurofeedback Trainingmentioning
confidence: 92%
See 2 more Smart Citations